Consumer Perceptions Of Web Site Quality: Indicators Of Customer Loyalty Intent - Kai, Seah Chong (2003)
The purpose of this study is to explore consumer\'s perception\'s of Web site quality and, therefore, to find out how we can achieve high customer retention, customer satisfaction, and profitability. This paper presents the results of a survey conducted to assess consumer perceptions and preferences for commercial Web sites.